Risk of malignancy in unilocular cysts: a study of 1148 adnexal masses classified as unilocular cysts at transvaginal ultrasound and review of the literature. (17th December 2012) - Valentin, L.; Ameye, L.; Franchi, D.; Guerriero, S.; Jurkovic, D.; Savelli, L.; Fischerova, D.; Lissoni, A.; Van Holsbeke, C.; Fruscio, R.; Van Huffel, S.; Testa, A.; et al.
ABSTRACT: Objectives: The aim of this study was to estimate the rate of malignancy in adnexal lesions described as unilocular cysts at transvaginal ultrasound examination and to investigate if there are differences in clinical and ultrasound characteristics between benign and malignant unilocular cysts. Methods: A total of 3511 patients with an adnexal mass underwent transvaginal ultrasound examination between 1999 and 2007. Sonologists used the International Ovarian Tumor Analysis terms and definitions to describe their ultrasound findings. Only masses operated on within 120 days after the ultrasound examination were included in the analysis and the histopathological diagnosis of the mass was used as the gold standard. Results: Of the 3511 masses, 1148 (33%) were classified as unilocular cysts on ultrasound. Of these, 11 (0.96% (95% CI, 0.48–1.71)) were malignant. The malignancy rate was lower in premenopausal than in postmenopausal women: 0.54% (5/931; 95% CI, 0.17–1.25) vs 2.76% (6/217; 95% CI, 1.02–5.92); P = 0.009. More patients with malignant unilocular cysts had a personal history of breast cancer (18% vs 2%; P = 0.02) or ovarian cancer (18% vs 0.6%; P = 0.003). Hemorrhagic cyst contents on ultrasound were more common in malignant than in benign unilocular cysts (18% vs 2%; P = 0.03). In seven of the 11 malignancies judged to be unilocular cysts at scan, papillary projections or other solid components were seen at macroscopic inspection of the surgical specimen. Conclusions: The malignancy rate in surgically removed adnexal lesions judged to be unilocular cysts at transvaginal scan is c 1%. Postmenopausal status, personal history of breast or ovarian cancer and hemorrhagic cyst contents on ultrasound increase the risk of malignancy. To avoid misclassifying adnexal lesions as unilocular cysts at scan, it is important to scrutinize unilocular cysts for the presence of solid components. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.